Management of Bottom Soils for Improving Water Quality and Fish pond Productivity - Patra, A.K.; Prakash, Chandra (Journal of Soil and Water Conservation, 2022)
Maintenance of a healthy aquatic environment and production of sufficient fish food Organisms in ponds are two factors of primary importance for successful pond cultural operations. Many methods are used in attempts to solve soil and water quality problems encountered in aquaculture. Amongst these, importance of bottom soils and their management has been presented in this article.